Comparative Pharmacodynamics of Telavancin and Vancomycin in the Neutropenic Murine Thigh and Lung Infection Models against Staphylococcus aureus - Lepak, Alexander J. (Antimicrob Agents Chemother, 2017)
The pharmacodynamics of telavancin and vancomycin were compared using neutropenic murine thigh and lung infection models. Four Staphylococcus aureus strains were included. The telavancin MIC ranged from 0.06 to 0.25 mg/liter, and the vancomycin MIC ranged from 1 to 4 mg/liter. The plasma pharmacokinetics of escalating doses (1.25, 5, 20, and 80 mg/kg of body weight) of telavancin and vancomycin were linear over the dose range. Epithelial lining fluid (ELF) pharmacokinetics for each drug revealed that penetration into the ELF mirrored the percentage of the free fraction (the fraction not protein bound) in plasma for each drug. Telavancin (0.3125 to 80 mg/kg/6 h) and vancomycin (0.3125 to 1,280 mg/kg/6 h) were administered by the subcutaneous route in treatment studies. Dose-dependent bactericidal activity against all four strains was observed in both models. A sigmoid maximum-effect model was used to determine the area under the concentration-time curve (AUC)/MIC exposure associated with net stasis and 1-log(10) kill relative to the burden at the start of therapy. The 24-h plasma free drug AUC (fAUC)/MIC values associated with stasis and 1-log kill were remarkably congruent. Net stasis for telavancin was noted at fAUC/MIC values of 83 and 40.4 in the thigh and lung, respectively, and 1-log kill was noted at fAUC/MIC values of 215 and 76.4, respectively. For vancomycin, the fAUC/MIC values for stasis were 77.9 and 45.3, respectively, and those for 1-log kill were 282 and 113, respectively. The 24-h ELF total drug AUC/MIC targets in the lung model were very similar to the 24-h plasma free drug AUC/MIC targets for each drug. Integration of human pharmacokinetic data for telavancin, the results of the MIC distribution studies, and the pharmacodynamic targets identified in this study suggests that the current dosing regimen of telavancin is optimized to obtain drug exposures sufficient to treat S. aureus infections.